PSD3 as a context-dependent modulator of immune landscape and tumor aggressiveness in esophageal squamous cell carcinoma - Luo, Shujuan; Li, Huifang; Cai, Bangwu; Nurbahati, Aididar; Cui, Hong; Peng, Tianyuan; Wang, Wei; Liu, Qing; Lu, Xiaomei; Zheng, Shutao (Frontiers in Immunology, 2025)
In this study, we investigated PSD3, CD274 (PD-L1), and TNFSF18 as potential immune-related biomarkers in esophageal squamous cell carcinoma (ESCC) using integrative transcriptomic and experimental approaches. CD274 and TNFSF18 were consistently up-regulated in ESCC across both TCGA and GEO datasets, while PSD3 showed significantly higher expression in TCGA but no significant difference in the GEO cohort. Only PSD3 demonstrated a significant association with overall survival, with higher expression correlating with improved prognosis. Interestingly, despite its favorable prognostic value, PSD3 functionally promoted ESCC cell proliferation, invasion, and migration in vitro, while inversely regulating PD-L1 expression. Conversely, heterozygous knockout of PD-L1 in KYSE150 cells impaired tumor aggressiveness. Co-immunoprecipitation revealed a direct physical interaction between PSD3 and PD-L1, suggesting a regulatory axis with implications for immune evasion. These findings position PSD3 as a context-dependent immuno-oncogenic factor and a potential therapeutic target in ESCC.